Diversity of insect pests in the dwarf country bean BARI Shim 5 grown during summer season in Barisal (Journal of the Bangladesh Agricultural University, 2026)
A study was carried out to record the prevalence and abundance of insect pests in the dwarf country bean (BARI shim-5) at Bangladesh Institute of Nuclear Agriculture, Barisal during March to June 2025. For this, seedlings were planted in the plastic plant growing pots. Insect pests were observed at four days interval in all leaves of all plants from seedling to fruiting stage and total thirteen (13) insects were recorded which were identified by matching with pictures, literature study and taking help from expert. The recorded insect pests were: bean armyworm, Spodoptera litura (Noctuidae: Lepidoptera); bean pod borer, Maruca vitrata (Crambidae: Lepidoptera); bean leaf folder, Omiodes indicata (Crambidae: Lepidoptera); red pumpkin beetle, Aulacophora foveicollis (Chrysomelidae: Coleoptera); spotted bean beetle, Pagria signata (Chrysomelidae: Coleoptera); pear-shaped weevil, Apion sp. (Apionidae: Coleoptera); bean leaf miner fly, Liriomyza sativae (Agromizidae: Diptera); bean thrips, Caliothrips fasciatus (Thripidae: Thysanoptera); kudzu bug, Megacopta cribraria (Plataspida: Hemiptera); black bean aphid, Aphis fabae (Aphididae: Hemiptera); jassids, Amrasca biguttula (Cicadellidae: Hemiptera); whitefly, Bemisia tabaci (Aleyrodidae: Hemiptera); and white leafhopper, Cofana spectra (Cicadellidae: Hemiptera). Among these, 3 insect belongs to Lepidoptera, 3 insect belongs to Coleoptera, 5 insect belongs to Hemiptera, 1 insect belongs to each Diptera and Thysanoptera order. Aphid was the most abundant (3.02 insects plant-1 observation-1) which was followed by whitefly (0.81 insects plant-1 observation-1) and bean thrips (0.57 insects plant-1 observation-1) while white leafhopper was least abundant (0.08 insects plant-1 observation-1) and was followed by bean leafhopper (0.08 insects plant-1 observation-1), and bean leaf miner (0.13 insects plant-1 observation-1). Therefore, the sucking pests were relatvely more abundant in the dwarf bean (BARI Shim-5) grown in Barisal.J Bangladesh Agril Univ 24(1): 14–22, 2026